Community service to increase red chilli economic value with post-harvest technology at Poktan Berkah Tani, Pulau Gambar Village, Serbajadi District, Serdang Bedagai District - sigalingging, Riswanti (Journal of Saintech Transfer, 2025)
In Indonesia, especially North Sumatra, chilli is a horticultural good that the people consume extensively. The availability and demand for red chillies in society are quite erratic; when production rises, the price of red chillies is rather low; when production falls, the price of red chillies will rise because of commodity shortage. Processing fresh chillies into chilli sauce, therefore, is one way to solve this issue. Making chillies into chilli sauce improves shelf life and sales value and makes sense for consumption, tastes great and refreshing, and accentuates the flavour of meals. Training courses on food safety for the Pulau Gambar people in Serbajadi District, Serdang Bedagai Regency, concentrated on chilli sauce processing technology and comprised the community service activities. The training sought to equip the residents with the tools required to create premium chilli sauce, which can be both a source of income and a way to support local cooking customs. Improving their understanding of food safety and processing methods will help the community to guarantee that their goods satisfy health criteria and also attract a larger market. This exercise seeks to guarantee the produced chilli sauce is fit for consumption. The approach was applied sauce. Of the 37 participants in the service activities, 100% said the outcomes were favourable; 69% (15 people) said they intended to try it themselves, and 31% said they were not sure yet.